Identification of a comprehensive set of transcriptional regulators involved in the long-term survivability of Escherichia coli in soil - Soma Nakamoto; Ikki Kobayashi; Koichi Watanabe; Takeru Kikuta; Sousuke Imamura; Tomohiro Shimada (Scientific Reports)
Abstract Bacteria that typically do not thrive in soil can survive therein for long periods. While much research has been conducted on the external environmental factors affecting the long-term survival of bacteria in soil, their inherent factors are poorly understood. To adapt to environmental changes, bacteria alter their gene expression patterns using transcriptional regulators such as sigma factors. Using Escherichia coli as a model bacterium, we examined the effects of each transcriptional regulator on the long-term survivability of E. coli in soil. The survivability of 294 E. coli strains deficient in transcriptional regulators in soil was measured over 6 weeks. The results showed that ten strains deficient in transcription factors significantly reduced survivability, whereas four deficient strains increased it. The functions common to several of these transcriptional regulators included carbon and nitrogen metabolism, stationary phase adaptation, and osmotic stress adaptation. These transcription factors are often global regulators and conserved among other pathogenic bacterial species. Taken together, we successfully identified a comprehensive set of transcription factors involved in the long-term survival of E. coli in soil. These findings will be useful for understanding the mechanisms underlying the adaptation of microorganisms to soil environments.